Pengembangan UMKM Produksi Tahu Desa Tulusbesar Melalui Pelatihan Dan Pendampingan Pengolahan Diversifikasi Produk Serta Penerapan Online Marketing - Djajanto, Ludfi; Kusmintarti, Anik; Wakhidah, Rokhimatul; Amerieska, Siti; Candrawati, Triesti; Asdani, Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Tulusbesar village is one of the villages in Tumpang sub-district, Malang district, where the livelihoods of the residents are mostly agriculture, animal husbandry and tofu production. Currently, tofu production MSMEs are one of the products being developed because they have potential and business opportunities and can improve the economic sector of Tulusbesar village. The aim of the community service program for tofu production MSMEs in Tulusbesar village is to help overcome the main problems that hamper the growth of tofu production MSMEs in Tulusbesar Village, such as the lack of diversification or product development with poor quality, the absence of management and bookkeeping activities. finances and promotional activities are still limited to word of mouth. The method of service activities applied is by conducting a problem survey, followed by analysis and implementation of problem solving with assistance and support for innovation and product diversification in accordance with consumer desires, providing assistance with machines and equipment that can improve the production process by combining appropriate technology and a touch of science and technology, business management training and financial bookkeeping and making packaging and labels as well as promotion through online marketing using social media such as Instagram. The results obtained from this community service include increased sales and product quality.